Lacquer chemistry and applications - Lu, Rong; Miyakoshi, Tetsuo (Amsterdam : Elsevier, 2015)
Lacquer Chemistry and Applications explores the topic of lacquer, the only natural product polymerized by an enzyme that has been used for a coating material in Asian countries for thousands of years. Although the human-lacquer-culture, including cultivation of the lacquer tree, harvesting, and the use of lacquer sap, has a long history of more than thousand years, there is very little information available on the modern scientific methods to study lacquer chemistry. This book, based on the results of the authors' 30 years of research on lacquer chemistry, offers lacquer researchers a unique reference on the science and applications of this extremely important material.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed August 10, 2015)
Elsevier
Keywords: Lacquer and lacquering; Wood finishing; Varnish and varnishing; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Lacquer and lacquering; Varnish and varnishing; Wood finishing; Electronic books